Evaluasi Tablet Effervescent Curcuma longa dan Tamarindus indica: Sifat Fisik, Analgesik, dan Toksisitas Akut - Farah Widya Kautsari; Maulida Rahmawati Emha (Universitas Hamzanwadi, 2026)
Dysmenorrhea was a common complaint among adolescent women and was often treated with nonsteroidal anti-inflammatory drugs (NSAIDs), although long-term NSAID use could cause adverse effects. Turmeric (Curcuma longa) and tamarind (Tamarindus indica) had traditionally been used in Indonesia as the “kunyit-asam” herbal preparation due to their anti-inflammatory and analgesic activities. However, traditional herbal drinks such as jamu godhog had several limitations, including inconsistent dosing and low stability, which supported the need for developing modern dosage forms like effervescent tablets. This study aimed to formulate and evaluate the physical quality and pharmacological activity of kunyit-asam effervescent tablets in three variations of turmeric extract concentrations, namely 250 mg, 500 mg, and 750 mg. The physical evaluations included organoleptic testing, weight uniformity, tablet hardness, and dissolution time, while pharmacological evaluations consisted of analgesic activity using the writhing test in male mice and acute toxicity testing to assess safety. The results showed that all three formulations met the required physical quality parameters. Analgesic testing indicated that doses of 2.6 mg/20 g BW and 3.9 mg/20 g BW produced analgesic effects comparable to paracetamol. Acute toxicity testing demonstrated that no mortality occurred in any treatment group. Overall, the developed kunyit-asam effervescent tablets exhibited good physical quality, were safe, and demonstrated potential as a modern herbal alternative for pain relief.